The impacts of transformational leadership on organizational outcome: Study in SMEs - Bujal, Siti Fatimah (2011)
Transformational leaders inspire followers to accomplish more by concentrating on the follower's values and helping the follower align these values with the values of the organization. The purpose of this literature review is to investigate the impact of the transformational leadership style on organizational outcomes. This review examines the following organizational outcomes: organizational citizenship behavior/performance, organizational culture, and organizational vision. By understanding the impact of transformational leadership on these outcomes, transformational leaders can influence employee behavior so that the behavior has a positive impact on the organization. One hundred and sixty eight respondents who working in small medium enterprises (SMEs) in different type of sectors participated in this study. A correlation test was used to investigate the relationship between transformational leadership style and organizational outcomes (organizational outcomes: organizational citizenship behavior/performance, organizational culture, and organizational vision). Regression analysis was carried out to examine the hypothesis and relationship between transformational leadership style and organizational outcomes.